Reimagining HR in the Age of Artificial Intelligence and Climate Change Adaptation - Joshi, Biva (Digital Repository of Theses - SSBM Geneva, 2025)
Experts’ perspectives on the use of advanced artificial intelligence (AI) as well as the necessity of adaptation to climate change mitigation measures in the workplace summon human resource (HR) professionals to view their impact directly on human capital, as constituted by multiple discussions by well-known think tanks, academia, and international organizations. Yet, since HR professionals in most organizations are rarely expected to tackle the multifaceted change strategically this power rests in fact on HR professionals to be aware of the rising trend, especially in these two areas and implement organizational change management efforts. To fully understand this dimension of the impact of AI and climate change on human capital, we must therefore understand the trending jobs and the literature behind the need for adaptation of human capital from both aspects. Reflecting on the analysis of publicly available data and with qualitative research on both fields, this research paper suggests ways in which human resource professionals can strategically identify potential threats, and primarily, opportunities for the newer type of jobs for human capital. This research will adopt an interdisciplinary approach of providing aid for HR professionals to foresee common impacts of the two most trending topics that are already showing signs of significant impact in jobs and then, take initiatives on change management approach to help human capital smoothly transition to newer types of jobs. Key words: artificial intelligence, climate change, human resources, change management.